Could Brain Decoding Machines Change Our Minds?. Issue 11 (November 2020) - Taschereau-Dumouchel, Vincent; Roy, Mathieu
Abstract : In a recent experiment, Zhang and colleagues designed a closed-loop brain–machine interface that learned to reduce participants' pain by decoding pain-related brain activity. In doing so, they also highlighted some of the challenges associated with coadaptive processes in brain–machine communication.